TRAUMATIC MEMORY OF DI/TII CONFLICT VICTIMS IN 1951-1966 AS MYSTICAL EXPERIENCE IN LEMBANG KADUAJA, TANA TORAJA, SOUTH SULAWESI - Rerung, Alvary Exan; Susanta, Yohanes Krismantyo (Penamas, 2024)
The DI/TII rebellion in Lembang Kaduaja, Tana Toraja, commanded by Kahar Muzakkar, was highly detrimental to the local population. The rebellion caused them to endure suffering until it became a traumatic memory for the community. We employed a qualitative approach to interpret the traumatic memory they interpreted as a spiritual experience. Therefore, phenomenological investigation is employed. The trauma memory will be examined from the perspective of Simone Weil and Dorothee Solle’s esoteric theology. The ideas of these two mystics will be compared and contrasted in order to demonstrate that the experience of suffering can also be interpreted as a form of intimacy and hospitality with God and others. Based on the dialogue, we conclude that the trauma memory experienced by the residents of Lembang Kaduaja is a supernatural event. The trauma memory encountered by the community teaches them the significance of living in peace. Tosangrapu and Siangkaran represent two dimensions of the Kaduaja community’s response to their mystic experience.